PENGENDALIAN KENAKALAN REMAJA MELALUI KEGIATAN KEAGAMAAN BERRBASIS SOLIDARITAS DI DESA JOGOMULYO KECAMATAN TEMPURAN KABUPATEN MAGELANG - Endang Sri Kurniatun; Lindra Kristiana (PPM Sdirjianbang Akademi Militer, 2023)
The adolescent transition period is a critical time for instilling moral values, character, religious basis, and scientific knowledge for their future. Regarding the life of adolescents who are vulnerable to delinquency that often disturbs families and communities, the religious activities of an adolescent are very influential on their lives and future. These errors that cause environmental distress are often referred to as juvenile delinquency